1983
DOI: 10.1177/0148607183007004346
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition in Malnourished Patients with Hepatic Cirrhosis and Acute Encephalopathy

Abstract: Ten patients with histologically proven cirrhosis, admitted in grade I to II acute hepatic coma, received in addition to a standard dietary protein free "anticoma" regime, a continuous nasogastric infusion of a branched-chain amino acid enriched chemically defined enteral diet (Hepaticaid) containing an equivalent of 70 g protein/day for a mean of 7.3 days (range 3-23). No complications of therapy were observed and, specifically, the use of fine bore tubes did not provoke variceal hemorrhage. Overall positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 8 publications
0
20
0
3
Order By: Relevance
“…25 51 Nevertheless, perforation of a pharyngeal or oesophageal pouch can occur and intracranial insertion of feeding tubes has been reported. 52 53 NG tube insertion should probably be avoided for three days after acute variceal bleeding 54 and although oesophageal, gastric, or small bowel perforation is unusual, it may occur if a guidewire is reinserted and accidentally exits via a side port. Perforation has also been reported when using polyvinyl or polypropylene tubes without guidewires.…”
Section: Tube Insertion Related Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 51 Nevertheless, perforation of a pharyngeal or oesophageal pouch can occur and intracranial insertion of feeding tubes has been reported. 52 53 NG tube insertion should probably be avoided for three days after acute variceal bleeding 54 and although oesophageal, gastric, or small bowel perforation is unusual, it may occur if a guidewire is reinserted and accidentally exits via a side port. Perforation has also been reported when using polyvinyl or polypropylene tubes without guidewires.…”
Section: Tube Insertion Related Complicationsmentioning
confidence: 99%
“…Larger tubes are also unsafe in the presence of varices even if they have not bled recently. 54 Post insertion tube related complications from gastrostomies and jejunostomies differ from those seen with NG and NJ tubes. [55][56][57][58][59][60][61] They include infection at the insertion site, peristomal leaks, accidental tube removal, tube fracture, gastro-colic fistula, peritonitis, septicaemia, and necrotising fasciitis.…”
Section: Post Insertion Tube Complicationsmentioning
confidence: 99%
“…The two lower doses were selected to see if a response could be obtained at a lower dose. The low dose of 150 mg /kg is similar to doses used in BCAA therapy for phenylketonuria, hepatic encephalopathy, and cirrhosis (Berry et al 1982(Berry et al , 1985(Berry et al , 1990Keohane et al 1983;Adibi 1984). The 180 mg /kg dose was selected to be midway between the high and low doses.…”
Section: Methodsmentioning
confidence: 99%
“…These Þndings suggest that the observed TD symptom remission was associated with greater availability of BCAA to the CNS, and a lessened availability of Phe (Richardson 1995;Richardson et al 1995Richardson et al , 1996. This suggestion, along with the literature demonstrating that BCAA medical foods have clinical utility in several disorders where the modulation of central LNAA concentrations is indicated (Berry et al 1982;Kern et al 1982;Keohane et al 1983;Adibi 1984;Horst et al 1984;Berry et al 1985Berry et al ,1990Egberts et al 1985;Fischer 1990;Gil et al 1990;Soreide et al 1991), led us to undertake the present study to test whether increasing the daily intake of the BCAA would decrease the symptoms of TD.…”
Section: Introductionmentioning
confidence: 95%
“…Subsequently other workers have confirmed these findings.2 At Central Middlesex Hospital, Keohane et al found a marked similarity between the nutritional status of patients admitted for management of complications of cirrhosis and those patients without liver disease who in the opinion of the nutritional support team required nutritional support. 4 Impaired dietary intake is almost certainly one ofthe principal causes for nutritional deficiencies in patients with chronic liver disease. "4 Documented mean protein and caloric intake was as low as 47 g/d and 1320 kcal/d2I respectively.…”
Section: B a Silk S J D O'keefe C Wicksmentioning
confidence: 99%